2015
DOI: 10.1177/1541931215591018
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in information search

Abstract: Past research often found that older adults searched less in terms of browsing and generating keywords; few studies examined the processes and underlying mechanism that caused the age-related reduction on search. In the current study, about 20 younger and 20 older adults performed ill-defined search tasks with a search box we implemented. In addition to the age differences in the quantities of search, results showed that there were qualitative age differences in allocating resources to exploration and exploita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…It has been shown that older adults choose less effective strategies than younger adults in other cognitive tasks and that these can lead to poorer performance (Brigham & Pressley, 1988; Lemaire, 2010; Price, Hertzog, & Dunlosky, 2008). In the present hybrid foraging example, this might be a strategic change in the trade-off between exploration and exploitation (Chin et al, 2015). Older adults seem to adopt a more conservative, exploitative strategy that encourages them to pick more targets than what is optimal if the goal is to maximize the rate of picking, taking time into account (which was the explicit instruction in the present experiment).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that older adults choose less effective strategies than younger adults in other cognitive tasks and that these can lead to poorer performance (Brigham & Pressley, 1988; Lemaire, 2010; Price, Hertzog, & Dunlosky, 2008). In the present hybrid foraging example, this might be a strategic change in the trade-off between exploration and exploitation (Chin et al, 2015). Older adults seem to adopt a more conservative, exploitative strategy that encourages them to pick more targets than what is optimal if the goal is to maximize the rate of picking, taking time into account (which was the explicit instruction in the present experiment).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies, however, should aim for larger samples with balanced gender distributions across age groups to control for potential sex differences in performance. Another question for future research is the generalizability of the age effects to other tasks that are not primarily visual and require strategic self-regulation, such as foraging-like behavior in internal information search (Chin, Anderson, et al, 2015; Hills & Dukas, 2012; Hills, Jones, & Todd, 2012; Pirolli, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 In search tasks, they exploit resources more than they explore new ones. 22 These reductions in risk‐taking and exploration behavior match the rise and fall of the dopaminergic system across the life span, with a deterioration of dopaminergic functioning in old age. 23 , 24 , 25 , 26 Therefore, when investigating exploratory behavior, it is relevant to take age into account.…”
Section: Introductionmentioning
confidence: 98%
“…Older adults show lower risk‐taking behavior and prefer familiar over novel options 21 . In search tasks, they exploit resources more than they explore new ones 22 . These reductions in risk‐taking and exploration behavior match the rise and fall of the dopaminergic system across the life span, with a deterioration of dopaminergic functioning in old age 23–26 .…”
Section: Introductionmentioning
confidence: 99%